Locating Nation: Interactions between Indonesians and Australians in Two Cultural Heritage Villages - Murti, Desideria Cempaka Wijaya (Curtin University, 2020)
This dissertation investigates ways of locating nation by exploring the expectations and experiences of Indonesians and Australian tourists at two cultural heritage villages in Indonesia. Drawing on concepts of imagined community, nation branding, and consumption of space, the project maps patterns of similarities, differences, and how these places are interconnected. Using a mixed methods approach of media analysis, ethnography, and discourse analysis, the thesis describes the complexity of the places, spaces, and nation.